The European refugee crisis and the natural rate of output - Katja Heinisch; Klaus Wohlrabe (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
The European Commission follows a harmonized approach for calculating structural (potential) output for EU member states that takes into account labor as an important ingredient. This paper shows how the recent huge migrants inflow to Europe affects trend output. Due to the fact that the immigrants immediately increase the working population but effectively do not enter the labor market, we illustrate that the potential output is potentially upward biased without any corrections. Taking Germany as an example, we find that the average medium-term potential growth rate is lower if the migration flow is modeled adequately compared to results based on the unadjusted European Commission procedure.
urn:nbn:de:gbv:3:2-66069
Keywords: F22; J11; J61; 330; migration; refugee crisis; natural rate of output; filtering; EU-commission